LIFE INSURANCE WITH COX PROPORTIONAL HAZARD REGRESSION AFFECTED BY AREAL SPATIAL FACTOR - Wulandari Aeli, Lita
Life insurance discusses about financial self-protection against uncertain events by focusses the state of the area of residence in addition to commonly used demographic information, such as age, gender, occupation, knowing certain diseases and others. Areal data contains postal codes, district/cities and regions. The application of the Weibull distribution to CoxPproportional Hazard regression can be used to describe the death and survival function for individuals living in a certain area by inputting spatial frailty effect. Spatial random effects on areal data are represented by a conditional autoregressive distribution that pay attention to the neighboring relationship of an area. The estimation of parameter values from the nitial model can be obtained by using Maximum Likelihood Estimation (MLE) and continuing with the Newton-Raphson optimization steps. The results of life insurance premiums without regard to random effects and with regard to random effects were simulated and applied to case data of accute myeloid leukemia in adults in North West England between 1982 and 1998 by the North West Leukemia Register in UK.